2019
DOI: 10.1007/s10067-019-04464-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of anti-keratin antibody for rheumatoid arthritis: a meta-analysis

Abstract: Objectives Anti-keratin antibody (AKA) is a serum antibody for patients with rheumatoid arthritis (RA), and it has a high specificity. Diagnostic role of AKA in RA was evaluated in this study. Methods PubMed, EMBASE, and Web of Science were searched to acquire eligible studies. Articles published before 15 March 2018 were considered to be included. Quality Assessment of Diagnostic Accuracy Studies 2 was used to evaluate the risk of bias and application concern of the included articles. Pooled analysis of diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Previous studies have found that the speci city of AKA in the diagnosis of RA is as high as 79-100%, while the sensitivity is 20-80% [6][7][8]. A meta-analysis of 2350 RA patients and 2067 control subjects showed that AKA had a sensitivity of 0.46 (95% CI 0.44-0.48) and a speci city of 0.94 (95% CI 0.93-0.95) for the diagnosis of RA, the diagnostic odds ratio was 15.86 (95% CI 9.48-26.52), and the area under the curve (AUC) was 0.7194 [9]. APF and AKA antibodies target the same antigen, epithelium laggrin [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that the speci city of AKA in the diagnosis of RA is as high as 79-100%, while the sensitivity is 20-80% [6][7][8]. A meta-analysis of 2350 RA patients and 2067 control subjects showed that AKA had a sensitivity of 0.46 (95% CI 0.44-0.48) and a speci city of 0.94 (95% CI 0.93-0.95) for the diagnosis of RA, the diagnostic odds ratio was 15.86 (95% CI 9.48-26.52), and the area under the curve (AUC) was 0.7194 [9]. APF and AKA antibodies target the same antigen, epithelium laggrin [10].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-MCV antibodies could also reflect disease activity ( 37 ) and predict radiological damage ( 38 ). Furthermore, AKA had a considerably high specificity for RA diagnosis ( 39 ). In our study, we not only explored the relationship between the proportion of Treg cells and their subsets and DAS28 [non-specific inflammatory indexes (ESR and CRP)] but also analyzed the relationship between Treg cells and RF, ACPA, or AKA status.…”
Section: Discussionmentioning
confidence: 99%
“…However, the composition of TCM is relatively complex, and the underlying mechanisms of TCM in regulating immunogenicity of patients with RA need further experimental verification. In addition, AKA is associated with RA disease activity, which can be used for the early diagnosis ( 29 ). AKA positive patients were more severe than negative patients in terms of joint swelling index, joint tenderness index, rest pain, morning stiffness time, and joint damage.…”
Section: Discussionmentioning
confidence: 99%